Malaria Parasite-Infected Erythrocytes Secrete PfCK1, the Plasmodium Homologue of the Pleiotropic Protein Kinase Casein Kinase 1 - Dorin-Semblat, Dominique (PLoS One, 2015)
Casein kinase 1 (CK1) is a pleiotropic protein kinase implicated in several fundamental processes of eukaryotic cell biology. Plasmodium falciparum encodes a single CK1 isoform, PfCK1, that is expressed at all stages of the parasite’s life cycle. We have previously shown that the pfck1 gene cannot be disrupted, but that the locus can be modified if no loss-of-function is incurred, suggesting an important role for this kinase in intra-erythrocytic asexual proliferation. Here, we report on the use of parasite lines expressing GFP- or His-tagged PfCK1 from the endogenous locus to investigate (i) the dynamics of PfCK1 localisation during the asexual cycle in red blood cells, and (ii) potential interactors of PfCK1, so as to gain insight into the involvement of the enzyme in specific cellular processes. Immunofluorescence analysis reveals a dynamic localisation of PfCK1, with evidence for a pool of the enzyme being directed to the membrane of the host erythrocyte in the early stages of infection, followed by a predominantly intra-parasite localisation in trophozoites and schizonts and association with micronemes in merozoites. Furthermore, we present strong evidence that a pool of enzymatically active PfCK1 is secreted into the culture supernatant, demonstrating that PfCK1 is an ectokinase. Our interactome experiments and ensuing kinase assays using recombinant PfCK1 to phosphorylate putative interactors in vitro suggest an involvement of PfCK1 in many cellular processes such as mRNA splicing, protein trafficking, ribosomal, and host cell invasion.